Functional characterization of ZjPYL8 from sour jujube: enhancing the sensitivity of stomata and roots to ABA in Arabidopsis thaliana - Peiyan Wang; Lanting Qi; Junna Song; Ruojia Zhu; Xiaowei Han; Yu Liu; Xianyun Wang; Yuguang Zheng; Zhao Liu (Acta Scientiarum Polonorum: Hortorum Cultus, 2023)
Abscisic acid (ABA) is a plant hormone that plays a crucial role in regulating plant growth, development, and adaptation to stress. The growth of Ziziphus jujuba Mill. var. spinosa (Bunge) Hu ex H. Chou, commonly known as Suanzao in Chinese, is significantly influenced by environmental factors, particularly drought and salt stresses. In this study, we isolated and characterized a putative ABA receptor, ZjPYL8, from Sour jujube. To investigate the effects of ZjPYL8 overexpression on ABA-responsive pathways, we introduced it into Arabidopsis thaliana (A. thaliana) and examined the resulting phenotypes. Our results demonstrated that overexpression of ZjPYL8 in A. thaliana led to a significant reduction in stomatal aperture and root length under ABA treatment, while the wild type (WT) was relatively insensitive to ABA. Moreover, ZjPYL8 transgenic plants exhibited shorter roots under salt treatment than the WT did. These findings suggest that the overexpression of ZjPYL8 in A. thaliana enhances the plant's resistance to stress and support the hypothesis that ZjPYL8 serves as a putative ABA receptor in Sour jujube, which may improve the plant's adaptability to drought and salt stresses. ZjPYL8 appears to mediate plant responses to ABA, similar to most ABA receptors in A. thaliana, such as stomatal closure and root length.